Uso do complexo químico sistêmico de cobre em aplicações de fungicidas no manejo da ferrugem asiática da soja - Lima, Jefferson Vasconcelos Oliveira de (2024)
The Brazilian crop protection market lacks better alternatives for best phytosanitary management. The agrochemicals life cycle has become increasingly shorter, making it peremptory to preserve the longevity of active ingredients. An adequate understanding of the compatibility of tank-mix in application is very important, as well as a better rotation of chemical groups in the management of diseases in soybeans. Another important point is about good coverage of applications, and the penetration and translocation of active ingredients in plants, as soybean is a crop with high leaf area index, favoring worsts coverages. The objective of this research was to study a new cupric formulation: the copper systemic chemical complex (CuSCC). According to its manufacturers, this product combined with other pesticides, can facilitate the translocation of active ingredients through plants, optimizing its. The quality of the tank-mix application, the management of Asian soybean rust, and the translocation of the active ingredients of three fungicides were studied. Among these three products, a new formulation was evaluated. In total, three surveys were carried out: 1) drop spectrum and physical-chemical properties of products: i) protioconazole + trifloxystrobin + bixafen; ii) tebuconazole + picoxystrobin + mancozebe and iii) fluxapyroxad + pyraclostrobin; 2) management of Asian soybean rust in soybeans with the same treatments and 3) translocations measures of active ingredients sprayed in the upper part of the crop to the unsprayed lower parts, by detection of compounds by chromatography (except mancozebe). All treatments having as comparisons with association and non-association with CuSCC. As results, CuSCC combined with fungicides increased the spray electrical conductivity, without significantly altering the pH, surface tension, spray stability, VMD, relative amplitude and the drops percent below 100 µm. Regarding the management of Asian soybean rust, CuSCC associated with the fungicides protioconazole + trifloxystrobin + bixafen and tebuconazole + picoxystrobin + mancozebe improved area under the disease progress curve (high and low parts), defoliation rates and productivity for two consecutive harvests. The addition of CuSCC favored the translocation of the active ingredients: protioconazole-desthio, trifloxystrobin, pyraclostrobin, picoxystrobin and tebuconazole, from upper sprayed parts to lower not sprayed parts, and did not difference only the translocation for bixafen and fluxapyroxad.